Graphene Oxide Sheathed ZIF-8 Microcrystals: Engineered Precursors of Nitrogen-Doped Porous Carbon for Efficient Oxygen Reduction Reaction (ORR) Electrocatalysis - Thomas, M.; Illathvalappil, R.; Kurungot, S.; Nair, Balagopal; Mohamed, A.; Anilkumar, G.; Yamaguchi, T.; Hareesh, U. (American Chemical Society, 2016)
© 2016 American Chemical Society.Nitrogen containing mesoporous carbon obtained by the pyrolysis of graphene oxide (GO) wrapped ZIF-8 (Zeolitic Imidazolate Frameworks-8) micro crystals is demonstrated to be an efficient catalyst for the oxygen reduction reaction (ORR). ZIF-8 synthesis in the presence of GO sheets helped to realize layers of graphene oxide over ZIF-8 microcrystals and the sphere-like structures thus obtained, on heat treatment, transformed to highly porous carbon with a nitrogen content of about 6.12% and surface area of 502 m2/g. These catalysts with a typical micromeso porous architecture exhibited an onset potential of 0.88Vvs RHE in a four electron pathway and also demonstrated superior durability in alkaline medium compared to that of the commercial Pt/C catalyst. The N-doped porous carbon derived from GO sheathed ZIF-8 core-shell structures could therefore be employed as an efficient electrocatalyst for fuel cell applications.